2015
DOI: 10.1016/j.pharep.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in endothelial theranostics

Abstract: The paper presents the recent advances in the development and studies of multifunctional nanoparticles which can be used to prevent/cure the cardiovascular diseases by detecting, treating and monitoring the early stages of atherosclerotic and thrombotic changes in endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…After intravascular administration, nanoparticles will initially contact the endothelium of the blood vessel, which is composed of a thin continuous layer of cell lining. The interaction of multifunctional nanoparticles with the endothelium is important,3842 as it is the main target in the treatment of disease, including inflammatory, cardiovascular and oncological diseases 43,44. PEG coating reduces adhesion of polystyrene spheres to endothelial monolayer under physiological shear in vitro 39.…”
Section: Introductionmentioning
confidence: 99%
“…After intravascular administration, nanoparticles will initially contact the endothelium of the blood vessel, which is composed of a thin continuous layer of cell lining. The interaction of multifunctional nanoparticles with the endothelium is important,3842 as it is the main target in the treatment of disease, including inflammatory, cardiovascular and oncological diseases 43,44. PEG coating reduces adhesion of polystyrene spheres to endothelial monolayer under physiological shear in vitro 39.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the use of molecular imaging with positron emission tomography (PET) has come into use. PET can more efficiently characterize brain tumors by investigating metabolic processes such as receptor binding, DNA synthesis or enzyme activity, oxygen metabolism and blood flow 54 - 57 . It is also observed that in comparison to other ailments, cancer is one of the most multifarious diseases with different phenotypic expressions at various organ sites.…”
Section: Current Approaches V/s Nanotheranostics For Brain Cancermentioning
confidence: 99%
“…Nanotheranostics can be also used for the management of atherosclerosis and its cardiovascular and cerebrovascular manifestations [17][18][19]. As with cancer, it is expected that multimodal nanoparticles will allow for non-invasive detection, long-term monitoring (for example using Fig.…”
Section: Opportunitiesmentioning
confidence: 99%